Sistem Informasi Jual Beli Kelapa Sawit Berbasis Web pada Peron Reskianto - Yasdomi, Kiki; Utami, Urfi; Maradona, Hendri; Dona, Dona; Rahayu, Susi (Jurnal Informatika, 2024)
In Surau Gading village, the majority of the population is employed as oil palm farmers. Every two weeks, farmers harvest oil palm fruit. After harvesting the oil palm fruit, the farmers sell it to Peron Resdianto, who is a young entrepreneur in the village of Surau Gading. Almost every day, the platform owner purchases agricultural products made from palm oil. Because a large number of customers sell their agricultural products, palm oil platform owners have to make sales to the factory once every two days. Once the palm oil mill receives the sales proceeds, the platform owner disburses payments to the palm oil farmers who sell their agricultural products. As information technology advances, it has now spread to almost all fields and is developing at a rapid pace. Information technology's application is evolving, as evidenced by the constant advancements in the field. The author wants to design a web-based information system for selling and buying palm oil on the Resdianto platform using the PHP and My SQL programming languages. We designed this system using system modeling tools, personal home page (PHP), MYSQL, HTML, data flow diagrams (DFD), Xampp, flowcharts, and entity relationship diagrams (ERD). Peron Reskianto can improve performance by creating a web-based information system for buying and selling palm oil, which will assist platform owners in collecting data on palm oil purchases and sales. This information system guarantees security and reduces errors.